IMPLEMENTASI PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN PAI - Alfiannur, Muhammad; Zulaikah, Eni; Cahyadi, Ani (Berajah Journal, 2024)
Teachers play an important role in helping students achieve the desired learning goals in learning activities. One of the main strategies used by educators is contextual learning. By using a contextual teaching and learning approach, students act as both subjects and objects. This method is not limited to the simple process of teachers conveying knowledge to students, but also involves students learning from their teachers. This research was conducted using qualitative methods through classroom observations, interviews with teachers and students, and analysis of learning documents. The research results show that the implementation of the contextual approach in PAI learning has been carried out well. This can be seen from the use of various contextual learning methods, such as group discussions, project-based learning, and problem-based learning. Teachers have also created a conducive learning atmosphere and motivated students to learn actively. The contextual approach has proven effective in improving PAI student learning outcomes. Students become more active and enthusiastic in learning and understand the lesson material more easily. Apart from that, students are also better able to apply religious values in everyday life.